Total Tanin, Fenol, Falvonoid, dan Antosianin Ekstrak Biji Kedelai Hitam (Glycine soja (L.) Merr.) dan Biji Kedelai Kuning (Glycine max(L.) Merr.) - Irma Erika Herawati; Siti Uswatun Hasanah; Hesty Nuur Hanifah; Lisna Dewi; Ita Inayah (Pharma Xplore : Jurnal Sains dan Ilmu Farmasi, 2025)
Soybeans were a unique type of legume because they contained important secondary metabolites, such as polyphenol compounds. Phenolic compounds were classified into several groups, including phenolic acids, flavonoids, tannins, and stilbenes, which had a common structure with multiple hydroxyl groups attached to a benzene ring. Epidemiological studies and meta-analysis data provided strong evidence that long-term consumption of polyphenol-rich products could help protect against cancer, cardiovascular diseases, diabetes, obesity, osteoporosis, and neurodegenerative diseases. The aim of this study was to analyze the flavonoid, phenol, tannin, and anthocyanin content in commercially available yellow and black soybean extracts. The extraction process was carried out using the maceration method. The total tannin and phenol content was determined using the Folin-Ciocalteu method, with tannic acid and gallic acid as standards. The total flavonoid content was measured using the AlCl₃ method with quercetin as the standard. Anthocyanin content was analyzed using the pH differential method. All measurements were conducted using a UV-Visible spectrophotometer. The results showed differences in the tannin, phenol, flavonoid, and anthocyanin content between black and yellow soybeans. Black soybeans had higher levels, with 0.074 mg/g (total tannin), 244 mg GAE/g (total phenol), 20.9 mg QE/g (total flavonoid), and 2.189 mg/100 mL (anthocyanin content).